A Changing Landscape in Castration-Resistant Prostate Cancer Treatment - Felici, Alessandra; Pino, Maria S.; Carlini, Paolo (Frontiers in Endocrinology, 2012)
Prostate cancer (PC) is the leading cause of cancer and the second leading cause of cancer-death among men in the Western world. About 10–20% of men with PC present with metastatic disease at diagnosis, while 20–30% of patients diagnosed with localized disease will eventually develop metastases. Although most respond to initial androgen-deprivation therapy (ADT), progression to castration-resistant PC (CRPC) is universal. In 2004 the docetaxel/prednisone regimen was approved for the management of patients with metastatic CRPC, becoming the standard first-line therapy. Recent advances have now led to an unprecedented number of new drug approvals within the past years, providing many new treatment options for patients with metastatic CRPC. Four new drugs have received U.S. Food and Drug Administration (FDA)-approval in 2010 and 2011: sipuleucel-T, an immunotherapeutic agent; cabazitaxel, a novel microtubule inhibitor; abiraterone acetate, a new androgen biosynthesis inhibitor; and denosumab, a bone-targeting agent. The data supporting the approval of each of these agents are described in this review, as are current approaches in the treatment of metastatic CRPC and ongoing clinical trials of novel treatments and strategies.